The Efficacy of Information and Communication Technology (ICT) Use in Islamic Religious Education Learning - Jirman, La Ode; Tobroni; Halik, Abdul; Hanafie, Wardah; Fahmi N. H. (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
This study aims to examine the effectiveness of Information and Communication Technology (ICT) use in Islamic Religious Education (PAI) learning at SMA Negeri 1 Baubau. The research employed a qualitative method with a descriptive approach. The vice principal, Islamic Religious Education teachers, and students of SMA Negeri 1 Baubau served as the primary data sources, while documents functioned as secondary data. Observation and interview guidelines were used as research instruments, and data were collected through in-depth interviews, participant observation, and documentation. Qualitative data were analyzed using data reduction, data display, and conclusion drawing or verification techniques. The findings indicate that ICT is implemented through interactive videos and digital presentations. Students reported that learning became more engaging through the use of e-learning applications, which enable them to study from home and access learning materials at any time. Furthermore, the results demonstrate that the use of ICT in Islamic Religious Education has the potential to significantly enhance students’ learning experiences, as learners show greater interest and improved comprehension of the material through e-learning platforms and instructional videos. However, challenges emerge when students and teachers are required to adapt to unfamiliar applications. Therefore, further training for teachers is necessary to optimize the use of ICT in the learning process. Overall, the study identifies supporting factors such as strong school commitment and adequate infrastructure, which positively contribute to ICT-based learning, as well as inhibiting factors, including unstable internet connections and difficulties in operating new applications, which may impede the optimal utilization of ICT. Abstrak: Penelitian ini bertujuan untuk menelaah efektivitas penggunaan Teknologi Informasi dan Komunikasi (TIK) dalam pembelajaran Pendidikan Agama Islam (PAI) di SMA Negeri 1 Baubau. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Wakil kepala sekolah, guru Pendidikan Agama Islam, dan siswa SMA Negeri 1 Baubau menjadi sumber data primer, sedangkan dokumen berfungsi sebagai data sekunder. Pedoman observasi dan wawancara digunakan sebagai instrumen penelitian, dan data dikumpulkan melalui wawancara mendalam, observasi partisipatif, serta dokumentasi. Data kualitatif dianalisis menggunakan teknik reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Hasil penelitian menunjukkan bahwa TIK diterapkan melalui video interaktif dan presentasi digital. Siswa melaporkan bahwa pembelajaran menjadi lebih menarik dengan penggunaan aplikasi e-learning, yang memungkinkan mereka belajar dari rumah dan mengakses materi pembelajaran kapan saja. Selain itu, hasil penelitian menunjukkan bahwa penggunaan TIK dalam Pendidikan Agama Islam berpotensi meningkatkan pengalaman belajar siswa secara signifikan, karena peserta didik menunjukkan minat yang lebih tinggi dan pemahaman materi yang lebih baik melalui platform e-learning dan video pembelajaran. Namun, tantangan muncul ketika siswa dan guru diharuskan menyesuaikan diri dengan aplikasi yang belum familiar. Oleh karena itu, pelatihan lanjutan bagi guru diperlukan untuk mengoptimalkan penggunaan TIK dalam proses pembelajaran. Secara keseluruhan, penelitian ini mengidentifikasi faktor pendukung seperti komitmen sekolah yang kuat dan infrastruktur yang memadai, yang berkontribusi positif terhadap pembelajaran berbasis TIK, serta faktor penghambat, termasuk koneksi internet yang tidak stabil dan kesulitan dalam mengoperasikan aplikasi baru, yang dapat mengurangi pemanfaatan TIK secara optimal.